Health Education Counseling In The Community About Diabetes Mellitus In The Working Area Of Puskesmas X In Bengkulu - Nurlindawati, Nurlindawati; Tari Puspita; Maria (Bengkulu Institute, 2024)
Diabetes can cause problems with various organs, with diabetic ulcers due to neuropathy being the most common, so the public must be educated about foot health care and foot exercises to prevent diabetic ulcers. The aim of this community service is to increase public awareness about diabetes mellitus. The method used in this activity is lecture, discussion. Leaflets are tools used to help deliver material. To find out how effective this activity was, an apperception was carried out to measure the participants' level of knowledge. After the activity is complete, questions are asked to carry out evaluation. The results of community service show that the educational method is effective in increasing respondents' knowledge about diabetes mellitus.